The good, the bad, and the ugly: a comprehensive study of temperament and personality traits as correlates of self-reported disruptive behavior problems in male and female adolescents - Muris, Peter; Bakker, Ireen; Peulen, Myrthe; van Mulekom, Sanne; Meesters, Cor (Frontiers in Child and Adolescent Psychiatry, 2023)
The aim of the present study was to provide a comprehensive picture of temperament and personality traits as correlates of self-reported disruptive behavior problems in male and female adolescents. Two-hundred-and-sixty-three non-clinical adolescents aged 12 to 18 years completed a survey containing standardized scales to measure the HEXACO personality traits, impulsivity, effortful control, Dark Triad traits, and symptoms of oppositional-defiant disorder (ODD) and conduct disorder (CD). The results showed that good traits (in particular, honesty-humility, agreeableness, and the regulative trait of effortful control) were negatively associated, while bad and ugly traits (especially impulsivity and the Dark Triad traits of psychopathy and Machiavellianism) were positively associated with symptoms of ODD and CD. In addition, regression analyses indicated that both types of disruptive behavior problems were associated with a unique set of temperament and personality correlates, and that specific correlates also differed for both genders. It is concluded that research on the role of temperament and personality should adopt a broad perspective, taking good, bad, and ugly traits from various theoretical models as well as gender differences into account.